Intensive care unit observation after pancreatectomy: Treating the patient or the surgeon?. Issue 5 (20th January 2022) - Sutton, Thomas L.; Potter, Kristin C.; O'Grady, Jack; Aziz, Michael; Mayo, Skye C.; Pommier, Rodney; Gilbert, Erin W.; Rocha, Flavio; Sheppard, Brett C.
Abstract: Background: Routine intensive care unit admission (ICUA) is commonplace following pancreatectomy, particularly pancreaticoduodenectomy. The value of this practice in avoiding failure‐to‐rescue is poorly studied. Methods: We queried our institutional National Surgical Quality Improvement Project database for patients undergoing pancreatectomy from 2013 to 2020. Postoperative dispositions, ICU courses, and hospital cost data in United States Dollars (USD) were captured. Data were analyzed with multivariable logistic regression. Results: Six‐hundred‐thirty‐seven patients were identified; 404 (63%) underwent pancreaticoduodenectomy. Postoperatively, 398 (99%) pancreaticoduodenectomies and 110 (47%) distal pancreatectomies had ICUA; two‐thirds ( n  = 318, 63%) did not require immediate postoperative ICU‐level interventions at ICUA. Of these, 17 (5.3%) subsequently required ICU‐level interventions during initial ICUA, most commonly antiarrhythmic infusion ( n  = 12). Thirty‐day and 90‐day mortality in patients requiring immediate ICU‐level interventions was 5% ( n  = 10) and 8% ( n  = 16) versus 0.3% ( n  = 1) and 1.2% ( n  = 4) in those without, respectively. Hospital length of stay was significantly longer with initial ICU‐level interventions (median 11 vs. 9 days, p  < 0.001), as were total ICU costs (mean 8683 vs. 14611 USD, p  < 0.001). Conclusion: At high‐volume pancreas centers, patients without immediate postoperative ICU‐level interventions are very low risk for failure‐to‐rescue. Ward admission with a low threshold for care escalation presents a significant opportunity for cost‐savings and un‐burdening ICUs.